THE EFFECT OF COMPARISON BETWEEN SOYBEAN EXTRACT AND JICAMA EXTRACT AND DURATION OF FERMENTATION ON SOYGHURT QUALITY - Naibaho, Benika; Hutagalung, Handaniel; Pandiangan, Samse (LPPM Universitas HKBP Nommensen, 2020)
Soyghurt is a fermented soy milk product using Streptococcus thermophilus and Lactobacillus bulgaricus bacteria. Efforts to enrich drinks high in antioxidants are carried out by combining food ingredients that can function as antioxidants such as soybeans and jicama. The combination of these two food ingredients and the assistance of the fermentation process by S. thermophilus and L. bulgaricans was expected to increase antioxidant activity in soyghurt production.This study used a completely randomized design (CRD) with 2 factors, namely: the first factor was the ratio of soybean juice and yam juice (S) which consisted of 4 treatment levels, namely: S0 = 100: 0, S1 = 75: 25, S2 = 50: 50, S3 = 25: 75, S4 0: 100. Meanwhile for the second factor was the duration of fermentation (F) which consisted of 3 levels of treatment, namely: F0 = 6 hours, F1 = 8 hours, F2 = 10 hours. The parameters observed were total solids, total acid, organoleptic value, antioxidant activity, and total lactic acid bacteria in jicama soyghurt on the best samples.The results showed that both treatment factors had a very significant effect (P <0.01) on total solids, total acid, and organoleptic tests of soyghurt. The study showed that the comparison of soybean juice and jicama juice and fermentation duration resulted a high protein content value of 9.18% and was in accordance with the SNI yoghurt protein content, namely minimum of 3.5%. Antioxidant activity of yam bean soyghurt obtained an IC 50 value of 18.110 mg / L and it was a very strong antioxidant. Total lactic acid bacteria on yam soyghurt was 108 CFU / ml and it was high.Based on this research results, it was suggested that soyghurt processing may use a combination with other types of fruits and use natural food coloring to give different flavors and increase the nutritional values of soyghurt.